2016
DOI: 10.1186/s12889-016-3236-1
|View full text |Cite
|
Sign up to set email alerts
|

Reductions in biomarkers of exposure, impacts on smoking urge and assessment of product use and tolerability in adult smokers following partial or complete substitution of cigarettes with electronic cigarettes

Abstract: BackgroundElectronic cigarettes (e-cigarettes) are popular alternatives to conventional cigarettes among adult smokers wishing to reduce their exposure to harmful smoke constituents. However, little information exists on the relative internal exposures resulting from the exclusive or dual use of e-cigarettes.MethodsMeasurements of product use; adverse events; changes in smoking urge; and blood, urine and exhaled breath biomarkers of exposure (BoE) representing toxicants believed to contribute to smoking relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 38 publications
5
50
1
Order By: Relevance
“…CO also was substantially reduced. O’Connel et al (219, 220), reported on a five day trial of 105 subjects confined to a clinical facility; they found similar reductions in the urinary biomarkers and CO. Lastly, a one-year clinical trial reported significant reductions in exhaled CO (221). Thus, compared to smoking, there appears to be a significant overall reduction in biomarkers for persons completely switching to e-cigs, but it is not known if these peripheral biomarkers reflect effects in the lung.…”
Section: Introductionmentioning
confidence: 90%
“…CO also was substantially reduced. O’Connel et al (219, 220), reported on a five day trial of 105 subjects confined to a clinical facility; they found similar reductions in the urinary biomarkers and CO. Lastly, a one-year clinical trial reported significant reductions in exhaled CO (221). Thus, compared to smoking, there appears to be a significant overall reduction in biomarkers for persons completely switching to e-cigs, but it is not known if these peripheral biomarkers reflect effects in the lung.…”
Section: Introductionmentioning
confidence: 90%
“…Of the 22 included studies, four were randomized controlled trials [9,[23][24][25], six were multi-institutional studies [8,[24][25][26], 10 were single-institutional studies, two analyses were of the US Population Assessment of Tobacco and Health [27,28], and one was an analysis of the National Health and Nutrition Examination Survey [29]. In addition, two pairs of studies reported results from common datasets [7,9,23,30] and four were sponsored by the tobacco or ecigarette industry [9,23,25,31]. Aggregation of the 22 studies produced an overall sample size of 1259 study participants, where individual sample study sizes ranged from 6 to 280.…”
Section: Study Sourcesmentioning
confidence: 99%
“…All 22 included studies were published since 2015. Participant mean/ median age was infrequently reported, but the median age of those reported was 36 yr [1,8,12,23,25,26,[31][32][33][34]. Study designs were primarily cross-sectional and longitudinal studies.…”
Section: Study Sourcesmentioning
confidence: 99%
“…Despite the absence of tobacco, many ingredients commonly included in e‐cigarette liquids can have harmful effects when inhaled, although exposure to aerosolized carcinogens and toxins may be decreased among e‐cigarette users compared with conventional cigarette users . Nicotine and other potentially harmful chemicals are also present in the aerosols emitted by e‐cigarettes, which could result in “secondhand” exposures to nonsmokers .…”
Section: Public Health Implications Of E‐cigarettesmentioning
confidence: 99%
“…4 Despite the absence of tobacco, many ingredients commonly included in e-cigarette liquids can have harmful effects when inhaled, 4,33,34 although exposure to aerosolized carcinogens and toxins may be decreased among ecigarette users compared with conventional cigarette users. 35,36 Nicotine and other potentially harmful chemicals are also present in the aerosols emitted by e-cigarettes, which could result in "secondhand" exposures to nonsmokers. 37 Beyond the chemical harms, there are concerns that e-cigarette use will lessen the negative attitudes and prohibitions that have developed in US society regarding cigarette use (ie, the potential to "normalize" cigarette smoking), 38 possibly leading to increased initiation or use of other types of tobacco products.…”
Section: Public Health Implications Of E-cigarettesmentioning
confidence: 99%